1972
DOI: 10.1080/03670244.1972.9990282
|View full text |Cite
|
Sign up to set email alerts
|

The socio‐cultural aspects of nutrition

Abstract: Man's nutritional behavior should be studied not only from the physiological and psychological standpoint but also from the socio-cultural point of view. Man is a social being, his deeply-rooted food habits have developed within a culture and they vary widely from one society to another. The socio-cultural factors bearing on food and nutrition range from material technologies to implicit ideologies and symbols, and are interrelated in an original pattern. Techniques such as food production, processing and cook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

1980
1980
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(35 citation statements)
references
References 11 publications
0
32
0
3
Order By: Relevance
“…This medical and scientific devaluation of the obese can be seen as part of a more Ethnicity. In many cultures obesity is associated with positive values, such as beauty, fertility and wealth, while in West European and US cultures, the opposite is the case (de Garine, 1972). The migration of approximately 500000 people from south-east Europe to Australia during the last 30 years provides the opportunity to compare the perceptions of adolescents from different ethnic backgrounds.…”
Section: Ascribed Roles Associated With Sex and Ethnicitymentioning
confidence: 98%
See 1 more Smart Citation
“…This medical and scientific devaluation of the obese can be seen as part of a more Ethnicity. In many cultures obesity is associated with positive values, such as beauty, fertility and wealth, while in West European and US cultures, the opposite is the case (de Garine, 1972). The migration of approximately 500000 people from south-east Europe to Australia during the last 30 years provides the opportunity to compare the perceptions of adolescents from different ethnic backgrounds.…”
Section: Ascribed Roles Associated With Sex and Ethnicitymentioning
confidence: 98%
“…Their view that FYW was strong and independent appears to be a traditional non-industrial view of fat women (de Garine, 1972). The SEP girls, along with the AP students, did not share this view.…”
mentioning
confidence: 93%
“…In sum, there are other significant benefits of having meals together with family, these include: positive socialization, information sharing and communication, family sustainability, family identity, commitment, learning of responsibility within the family, better physical health, and healthier eating habits (Larson, Branscomb, and Wiley 2006;Blum-Kulka 1997;Lewis and Feiring 1982;DeGarine 1972;Ochs and Shohet 2006;Fiese, Foly, and Spagnola 2006;Larson and Richards 1994). Past literature across multiple disciplines indicates that eating together with family is not only beneficial for children's socialization, but also has strong correlations with self-regulation.…”
Section: Eating Meals Togethermentioning
confidence: 99%
“…A number of studies have indicated that traditional cultural beliefs and practices relating to diet still have an important role in food selection, even in traditional communities undergoing modernization (Tan et al 1970, de Garine 1972, Manderson 1986). This is also the case in Bali (Gunung et al 1981, Cole 1983, Huntsman 2002.…”
Section: Discussionmentioning
confidence: 98%